STI Profile and Treatment Seeking Behavior Of Street Children In Surat - NB Patel; RK Bansal (Medsci Publications, 2010)
This cross-sectional study among 326 street children using a pre-tested interview schedule reveals that 50.5% of children with a history of having had sex, had a history suggestive of STI infections during the past six months with the commonest symptom was a painless single ulcer (29.1%). All of them had sought treatment, albeit irregular and incomplete, even in personally supervised conditions, owing to reasons as external relief from symptoms with significantly improved medical care behaviors consequent to repeatedly cajoling. was sometimes construed as cure by the street children, for instance after one or two injections, these children get so much relief that they feel that they have been cured and then they do not come for the remaining treatment. When many of these children perceive that their disease has cured, they desist from further treatment even when they are informed that the treatment that they have received is incomplete and that they are still suffering from the disease till they take the full course of treatment. Some of them eventually do heed to repeated cajoling, for instance, one child who had tested positive for HIV now takes regular treatment from New Civil Hospital, Surat. The majority seek treatment at public facilities where though the cost of treatment is less the behaviour of the staff is often unsatisfactory and the children feel stigmatized and ashamed and this along with some additional reasons prompts them to seek medical care from chemists and not qualified allopathic doctors ignorant in proper STI management with serious concerns. The study reveals important insights into their concepts of cure, choosing of treatment venues and counselling received during treatment.